PETRAS: a socio-technical framework for Internet of Things research and development - Ogunniye, Gideon; Hana, Amaya; Watson, Jeremy (Frontiers in the Internet of Things, 2024)
This paper presents a case application of a socio-technical framework for Internet of Things (IoT) research and development in the United Kingdom. Applying a socio-technical system approach to IoT, this paper seeks to provide a clear understanding of the interplay between technical and non-technical aspects of IoT research and development. It describes the socio-technical requirements for IoT design and development and provides the current snapshot of research in the United Kingdom to meet these requirements. Finally, the paper provides useful information on how to conceptualize IoT research within human-centered contexts and a useful guide for centre design and evaluation to those developing new research centres or seeking to reinvigorate existing ones.